Direct probing of band-structure Berry phase in diluted magnetic semiconductors - Granada, Mara (2015)
We report on experimental evidence of the Berry phase accumulated by the charge-carrier wave function in single-domain nanowires made from a (Ga, Mn)(As, P) diluted ferromagnetic semiconductor layer. Its signature on the mesoscopic transport measurements is revealed as unusual patterns in the magnetoconductance that are clearly distinguished from the universal conductance fluctuations. We show that these patterns appear in a magnetic field region where the magnetization rotates coherently and are related to a change in the band-structure Berry phase as the magnetization direction changes. They should thus be considered a band-structure Berry phase fingerprint of the effective magnetic monopoles in the momentum space. We argue that this is an efficient method to vary the band structure in a controlled way and to probe it directly. Hence, (Ga, Mn)As appears to be a very interesting test bench for new concepts based on this geometrical phase.